1965
DOI: 10.1126/science.150.3694.348
|View full text |Cite
|
Sign up to set email alerts
|

Visual Contours in Homogeneous Space

Abstract: With the aid of the Julesz figures, we introduce the concept of the stereoscopic edge, an edge which exists visually in the absence of physical contours. This edge, as well as the full complex of normal stereoscopy, can be present in the complete absence of physical contours at the fovea to approximately +/- 3.00 degrees from fixation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

1965
1965
1995
1995

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(16 citation statements)
references
References 12 publications
2
14
0
Order By: Relevance
“…When it is viewed stereoscopically, the central white square appears to float forward of the background, the square itself being defined (as in the situation where the figure is viewed monocularly) by subjective contours. These subjective contours are similar to the anomalous contours described by Lawson and Gulick (1967) and by Shipley (1965); however, in this case, the contours can be seen under monocular as well as under stereoscopic viewingconditions. …”
supporting
confidence: 82%
“…When it is viewed stereoscopically, the central white square appears to float forward of the background, the square itself being defined (as in the situation where the figure is viewed monocularly) by subjective contours. These subjective contours are similar to the anomalous contours described by Lawson and Gulick (1967) and by Shipley (1965); however, in this case, the contours can be seen under monocular as well as under stereoscopic viewingconditions. …”
supporting
confidence: 82%
“…Frisby and Clatworthy (1975) therefore suggested that illusory figures produced by lateral disparity may be different from monocularly induced apparent depth. The finding by Mustillo and Fox (1986) that sharp illusory contours can be observed in Kanizsa-type random-dot stereograms which are completely devoid of monocular brightness cues makes the same point (see also Shipley 1965;Julesz and Frisby 1975;Prazdny 1985). These problems are currently being investigated by psychophysicists and computational vision scientists.…”
Section: Illusory Contours As Intelligent Solutions To Perceptual Promentioning
confidence: 87%
“…Similarly, Ullman (1976), Marr (1976Marr ( , 1982, and Zucker and Cavanagh (1985) suggest that there are filling-in mechanisms in early vision which rely essentially on the processing of local cues and operate before an interpretation of the image takes place. In a natural environment, local cues for occlusion are readily available at line ends and other sharp discontinuities, eg T-junctions formed by branches (Kennedy 1988;Shipley andKellman 1990, 1992a;Kellman and Shipley 1991;Peterhans and von der Heydt 1991;Enns and Rensink 1994;Dresp, submitted).…”
Section: The Biological Significance Of Illusory Contoursmentioning
confidence: 99%
See 1 more Smart Citation
“…Shipley (1965) has shown that even in blurred or out-of-focus configurations, the sharp subjective contour still accompanies the perception of the central form in depth. Lawson and Gulick (1967) extended the analysis of subjective contours seen in these patterns.…”
Section: Binocular Disparity and Subjective Contourmentioning
confidence: 99%